Pengaruh Refugia Terhadap Keberadaan Hama Ulat Grayak (Spodoptera exigua Hbn.) Pada Tanaman Bawang Merah di Kabupaten Enrekang - Riskiani; Rifni Nikmat Syarifuddin; Trisnawaty AR (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2025)
Shallots (Allium cepa L.) is one of the important vegetable commodities that many people need as a seasoning for cooking. Shallot production in South Sulawesi region experienced a significant decline from 2021 to 2022, namely from 183.210 tons to 175,160 tons (BPS 2023). In the cultivation process, shallots are susceptible to pest attacks. One of the main pests that causes a decrease in shallot productivity is the onion caterpillar (Spodoptera exigua Hbn.). This research will be carried out in Potokullin Village, Buntu Batu District, Enrekang Regency, South Sulawesi and BRMP Laboratory (Agricultural Assembly and Modernization Agency), in March 2025-July 2025. This research activity uses a random group design consisting of 5 treatments, namely without refugia (P0) as a control, marigold (P1), zinnia (P2), virgin footprint (P3), a combination of marigold plants, zinnia and virgin footprint (P4). Each treatment is repeated 4 times and each repetition consists of 9 plants so that the number of observation units is 180 plants. The results showed that treatment without refugia (P0) showed the highest density of caterpillar population (0.58) and was markedly different from Zinnia refugia treatment (P2) which had the lowest density (0.28). Meanwhile, the results of the attack intensity shows that treatment without refugia (P0) produces the highest attack intensity of caterpillars, which is 61% in the very high category and is markedly different from the use of refugia, especially the combination (P4) and Zinnia (P2) with an attack intensity of 28% in the medium category.